A control method for flow rate distribution of cracked hydrocarbon fuel in parallel channels. (25th July 2016) - Jiang, Yuguang; Zhang, Silong; Feng, Yu; Cao, Jie; Qin, Jiang; Bao, Wen
Highlights: Mal-distribution of coolant causes a waste of heat sink and even over-temperature. A flow control method based on tandem flow restriction was brought up and validated. The connect between fluid property and the control effect was studied. The pressure drop of the method was presented and analyzed. Abstract: With the development of hypersonic vehicles, regenerative cooling becomes an effective method of thermal protection, in which fuel is thus used as coolant. However, it presents the problem of fuel mal-distribution and the waste of heat absorption capacity. In this work, a flow control method based on tandem flow restriction is brought up and experimentally studied with a two-parallel-pipe system. The variation of control effect with different position and corresponding fuel temperature of the restrictors is analyzed. Compared with the single flow restriction, tandem flow restriction method achieves better control effect and allows larger flow restrictors with lower and self-adaptive pressure drop. The fuel heat sink utilization will be improved by proposed effective method for flow rate distribution and corresponding recuperation effectiveness of the engine cycle is improved.